Bile Acid Synthesis in the Isolated, Perfused Rabbit Liver - E. H. Mosbach; M. A. Rothschild; I. Bekersky; M. Oratz; J. Mongelli (The Journal of Clinical Investigation, 1971)
These experiments were carried out to demonstrate the usefulness of the perfused rabbit liver for studies of bile acid metabolism, and to determine the rate-limiting enzyme of bile acid synthesis. Rabbits were fed a semisynthetic diet, with or without the addition of 1% cholestyramine, under controlled conditions. At the end of 2-5 wk, the livers were removed and perfused for 2.5 hr employing various 14C-labeled precursors to measure de novo cholic acid synthesis. The livers were then analyzed for cholesterol, and the bile collected during the perfusion was analyzed for cholesterol and bile acids. Control bile contained, on the average, 0.34 mg of glycocholate, 7.4 mg of glycodeoxycholate, and 0.06 mg of cholesterol. After cholestyramine treatment of the donor rabbits, the bile contained 3.3 mg of glycocholate, 3.7 mg of glycodeoxycholate, and 0.05 mg of cholesterol. It was assumed that in cholestyramine-treated animals the enterohepatic circulation of the bile acids had been interrupted sufficiently to release the feedback inhibition of the rate-controlling enzyme of bile acid synthesis. Therefore, a given precursor should be incorporated into bile acids at a more rapid rate in livers of cholestyramine-treated animals, provided that the precursor was acted upon by the rate-controlling enzyme. It was found that the incorporation of acetate-14C, mevalonolactone-14C, and cholesterol-14C into cholate was 5-20 times greater in the livers of cholestyramine-treated animals than in the controls. In contrast, there was no difference in the incorporation of 7α-hydroxycholesterol-14C into cholate regardless of dietary pretreatment. It was concluded that given an adequate precursor pool, the 7α-hydroxylation of cholesterol is the rate-limiting step in bile acid formation.